UJI PERFORMA MESIN MENGGUNAKAN BAHAN BAKAR PERTAMAX DAN PERTAMAX TURBO PADA MESIN 4 LANGKAH - CAHYA NEGARA, ABDI MUHAMMAD; Atmanto, Ireng Sigit; Mrihardjono, Juli (universitas teuku umar, 2023)
Performance and vehicle exhaust emissions are determined by many factors that come from various components and take place in a related manner. This test uses 4 types of motorcycles with different cylinder volumes. The test was conducted using a dynamometer test equipment. How to test on a dynamometer using fuel pertamax and Pertamax turbo. Data were taken on transmission gears 1, 2, 3 and 4 at speeds of 20 km, 40 km and 60 km. For emission testing follows the procedure of taking power and torque data and performed simultaneously.The content of emissions in the exhaust gas is CO, CO2, HC and O2 based on the results of the use of exhaust emissions test equipment.The relationship between vehicle speed and gear position to power, torque and exhaust emissions on 2 different fuels is the higher the transmission gear position and speed, the result is high, namely on pertamax fuel (power, torque, CO gas emissions) and pertamax turbo (Power, Torque, CO gas emissions, CO2 gas), the lower the transmission gear position and speed, the result is high, namely on pertamax fuel (CO2) and the lower the transmission gear position and speed, the result is high, namely HC on pertamax fuel and pertamax turbo.The test results of statistical tests t-test 2 samples obtained the results of the fuel test pertamax = Pertamax turbo fuel test on 4 vehicles with different cylinder volumes. Exceptions exist in 160 cylinder volume vehicles in the HC test and 125 cylinder volume vehicles in the CO2 test.